Effectiveness of Insect Encyclopedia E-Book With Mind Mapping Strategy to Train Students' Creative Thinking Skills - Amin Dwi Cahyanti; Elok Sudibyo; Yuni Sri Rahayu (IJORER : International Journal of Recent Educational Research, 2021)
As technology advances, learning materials in learning are expected to be able to apply technological developments and practice the skills needed in the 21st century, namely communication and creative thinking. E-book, which was developed with a mind mapping strategy, is equipped with various features that can support student creativity. This study aims to produce an insect encyclopedia e-book with a mind mapping strategy to practice creative thinking skills for class X Senior High School which is declared effective. The effectiveness of the insect encyclopedia e-book in terms of learning outcomes, mind mapping skills and student responses. Creative thinking skill can be used to solve the problems and develop the idea. The method used is a modified research and development (R&D) method. The data collection technique was through validation, observation, questionnaires and tests. The data analysis technique was carried out quantitatively. Based on the results of the study, the average score of student learning outcomes was 82.60% and the N gain value was 0.50 in the medium category. The average score of students' mind mapping skills in the high category. And reviewed based on the skills of making mind mapping with good categories and based on student responses positively.